2017
DOI: 10.1002/cbf.3303
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid protects cardiomyocytes against cobalt chloride induced hypoxia by regulating transcriptional mediator of cells stress hypoxia inducible factor 1α and p53 protein

Abstract: In hepatocytes, ursodeoxycholic acid (UDCA) activates cell signalling pathways such as p53, intracellular calcium ([Ca ] ), and sphingosine-1-phosphate (S1P)-receptor via Gα -coupled-receptor. Recently, UDCA has been shown to protect the heart against hypoxia-reoxygenation injury. However, it is not clear whether UDCA cardioprotection against hypoxia acts through a transcriptional mediator of cells stress, HIF-1α and p53. Therefore, in here, we aimed to investigate whether UDCA could protect cardiomyocytes (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…[14,17] On the other hand, in addition to the conduction, it also decreases the activation of p53 and HIF-1 alpha activation which are the factors responsible for tissue damage during the hypoxia in cardiac myocytes. [18] In consistent with the literature, we found in our study that the prolonged fetal AV conduction time associated with the obstetric cholestasis was shortened by UDC treatment. [15] MPI shows both systolic and diastolic cardiac functions.…”
Section: Discussionsupporting
confidence: 92%
“…[14,17] On the other hand, in addition to the conduction, it also decreases the activation of p53 and HIF-1 alpha activation which are the factors responsible for tissue damage during the hypoxia in cardiac myocytes. [18] In consistent with the literature, we found in our study that the prolonged fetal AV conduction time associated with the obstetric cholestasis was shortened by UDC treatment. [15] MPI shows both systolic and diastolic cardiac functions.…”
Section: Discussionsupporting
confidence: 92%
“…Taurocholic acid is a taurine-conjugated hydrophobic BA that has been reported as a partial agonist of the muscarinic M2 receptor (Gαi-coupled receptor), which induces arrhythmia in cultured CMs [62]. In agreement with Sheikh Abdul Kadir et al [62], Mohamed et al [93] reported that UDCA maintains the normal intracellular [Ca 2+ ] i dynamics against hypoxic condition, which is also mediated by Gαi-coupled receptor. Gorelik et al [94] showed that UDCA protects the heart from TC-induced arrhythmias by improving contraction and calcium dynamic changes in CMs.…”
Section: Ursodeoxycholic Acid Protects the Heart Against More Hydrmentioning
confidence: 69%
“…In addition, S1P3 receptors are expressed in the heart, and its activation results in bradycardia [127]. Mohamed et al [93] reported that UDCA’s protection of CMs against hypoxia could be mediated partly by S1P1 receptor. The study suggested that cardioprotection of UDCA was observed to be similar to FTY720 (S1P receptor agonist) in inhibiting the lethal effect of hypoxia through inhibition of HIF-1α and p53 protein and restoration of normal [Ca 2+ ] i in hypoxic CMs [93].…”
Section: Past Current and Future Perspectives On Role Of Ursodeomentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to p53 translocation into the cytoplasm which promotes its degradation by the proteasome. Mohamed et al, [123] has shown that UDCA inhibits the upregulation of p53 and hif-1α in hypoxic cardiomyocytes. HIF-1 is used to target many genes such as p53, VEGF, nitric oxide synthase, PDK1 in mediating tumor metastasis, angiogenesis, energy metabolism and metabolic adaptation.…”
Section: Cardioprotectionmentioning
confidence: 99%